Transregional Connectivity of Muslim Fashion Between Indonesia and Arab Paninsula: A Literature Review - Prayogi, Bagus; Ramadhani, Muhammad Akbar; Arwanto, Adelina Nurianingtyas; Ashari, Nesha Risky (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2025)
Muslim fashion has always seemed to be identified with Arabia as the birthplace of Islam, especially in Indonesia which is considered a fringe area from the spread of Islam. Even though Muslim fashion can be negotiated with the existing locality. Not only that, the value of locality has a great impact as a transregional offer as another differentiation of Muslim fashion. Of course, this will support the ideals of Indonesia which wants to be the mecca of Muslim fashion in the future. So from these problems, the first formulation of the problem offered, how is Muslim fashion contestualized with locality? Second, How is the transregional connectivity of Muslim fashion emerging in today's dynamics? Third, is there any past intervention or residue on the populist Muslim fashion today? This research is a qualitative research with the type of library research. The purpose of this study is to first analyze Muslim fashion contestualized with locality. Second, to analyze the transregional connectivity of Muslim fashion that has emerged in the current dynamics. Third, analyze past interventions or residuals against the populist Muslim fashion today.